International security studies theory and practice - Hough, Peter 1967- (Routledge Taylor & Francis, 2015)
This new textbook provides students with a comprehensive and accessible introduction to the subject of security studies, with a strong emphasis on the use of case studies. In addition to presenting the major theoretical perspectives, the book examines a range of important and controversial topics in modern debates, covering both traditional military and non-military security issues, such as proliferation, humanitarian intervention, food security and environmental security. Unlike most standard textbooks, the volume also offers a wide range of case studies - including chapters on the USA, China, the Middle East, Russia, Africa, the Arctic, the Middle East, Europe and Latin America - providing detailed analyses of important global security issues. The 34 chapters contain pedagogical features such as textboxes, summary points and recommended further reading and are divided into five thematic sections: - Conceptual and Theoretical - Military Security - Non-Military Security - Institutions and Security - Case Studies This textbook will be essential reading for all students of security studies and highly recommended for students of critical security studies, human security, peace and conflict studies, foreign policy and International Relations in general